2015
DOI: 10.1017/s0007114515000732
|View full text |Cite
|
Sign up to set email alerts
|

A high-cholesterol diet enriched with polyphenols from Oriental plums (Prunus salicina) improves cognitive function and lowers brain cholesterol levels and neurodegenerative-related protein expression in mice

Abstract: Ageing accompanied by a decline in cognitive performance may be a result of the long-term effects of oxidative stress on neurologic processes. It has been shown that high-cholesterol contents in the blood and brain may lead to the deposition of the b-amyloid (Ab) protein in the brain, which damages brain cells. The present study was designed to observe the effect of polyphenol-rich Oriental plums on cognitive function and cerebral neurodegeneration-related protein expression in mice that were fed a high-choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 33 publications
2
29
1
Order By: Relevance
“…In our experiment, despite an approximately fourfold increase in TC plasma levels, we observed no marked change in brain TC. These findings are in contrast to another study (14), which showed that cholesterol concentrations in both blood and brain were significantly higher in the HC group than in the control group. It should be noted that in that study 5% cholesterol was administered in comparison with the 2% cholesterol dose in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our experiment, despite an approximately fourfold increase in TC plasma levels, we observed no marked change in brain TC. These findings are in contrast to another study (14), which showed that cholesterol concentrations in both blood and brain were significantly higher in the HC group than in the control group. It should be noted that in that study 5% cholesterol was administered in comparison with the 2% cholesterol dose in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…To elucidate the effect of a high cholesterol diet on APP processing, we assayed the expression of BACE1 in the hippocampus homogenates of rats and found a significant increase in the hippocampal expression of BACE1. In support of our findings, Kuo et al have also reported a significant increase in the mRNA expression of CYP46A1, BACE1 and 24S-OHC levels in the hippocampus and brain cortex (14). In another study, Ghribi et al (36) demonstrated that feeding rabbits with 1% cholesterol for 7 months led to increased levels of BACE1.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Kuo et al reported that treating mice with a high-cholesterol diet enhanced serum and brain cholesterol concentrations, and elevated TBARS content in serum. Furthermore, highcholesterol diet-treated mice exhibited cognitive dysfunction in the Morris water maze test (27). Ettcheto et al described the relationship between hypercholesterolemia and neurodegeneration using low density lipoprotein (LDL) receptor knockout and amyloid precursor protein (APP)/presenilin (PS) 1 transgenic mice (28).…”
Section: The Possible Role Of Vitamin E Deficiency-induced Elevated Smentioning
confidence: 99%
“…Instead, recent findings have suggested that in lower amounts, typical of those attained in the diet, polyphenols may exert pharmacological activity within the cells with mechanisms that go beyond the classic antioxidant scavenging mechanisms (Williams et al, 2004;Vauzour et al, 2010). In particular, polyphenols are capable of modulating intracellular signalling cascades Vauzour et al, 2010;Kuo et al, 2015), gene expression and interactions with mitochondria (Schroeter et al, 2001;Schroeter et al, 2007;Vauzour et al, 2007b;Mandel et al, 2008). By affecting such pathways, they have the potential to induce new protein synthesis in neurons and thus an ability to induce morphological changes, which have a direct influence on memory acquisition, consolidation and storage.…”
Section: Effects Of Polyphenols On Age-related Cognitive Decline and mentioning
confidence: 99%